2020
DOI: 10.1111/eve.13433
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory capacity of the Thoroughbred racehorse and its relationship to the pathogenesis of exertional heat illness

Abstract: Summary When racehorses fail to thermoregulate effectively, whether due to intrinsic or extrinsic factors, a condition called exertional heat illness (EHI) may occur, which can be life‐threatening and represents a significant welfare issue. Horses usually become affected in the recovery phase soon after racing, so that a knowledge of the ‘normal’ thermoregulatory processes which operate at this time and their variations is essential to enable early detection of EHI. Racing in hot or warm and humid weather cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The identification of ongoing hyperthermia during recovery is essential information with respect to equine welfare and emphasizes the need for extended continuous monitoring post-exercise. Our findings may explain personal anecdotal evidence expressed by trotter trainers noticing that some horses show discomfort the day after an otherwise uneventful competition day ( Courouce et al, 2002 ; Richard et al, 2010 ; Bertuglia et al, 2014 ) due to unrecognized post-racing hyperthermia ( McConaghy et al, 2002 ; Brownlow and Mizzi, 2020 , 2021 ). The current findings also underline that the habit of withholding water prior to racing events is not an ideal practice.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The identification of ongoing hyperthermia during recovery is essential information with respect to equine welfare and emphasizes the need for extended continuous monitoring post-exercise. Our findings may explain personal anecdotal evidence expressed by trotter trainers noticing that some horses show discomfort the day after an otherwise uneventful competition day ( Courouce et al, 2002 ; Richard et al, 2010 ; Bertuglia et al, 2014 ) due to unrecognized post-racing hyperthermia ( McConaghy et al, 2002 ; Brownlow and Mizzi, 2020 , 2021 ). The current findings also underline that the habit of withholding water prior to racing events is not an ideal practice.…”
Section: Discussionmentioning
confidence: 63%
“…Exertional heat illness (EHI) in horses is characterized by severe central nervous system dysfunction, such as physical collapse, and has been described in detail ( Brownlow et al, 2016 ; Brownlow and Mizzi, 2020 ). Recently, a Japanese study identified a wet-bulb globe temperature (WBGT) index above 28°C to be responsible for a 28.5% higher risk for development of EHI when compared to the index below 20°C ( Takahashi and Takahashi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MH produced during exercise needs to be dissipated from the horse to the surrounding environment through four main pathways, namely, radiation, conduction, convection, and evaporation, the last being the most essential and pivotal pathway in horses ( 23 , 48 , 53 56 ). Evaporation from the body surface is mainly achieved by increased blood flow, cutaneous vasodilation followed by evaporation of sweat from the skin (70–85% of the MH load) ( 25 , 48 , 54 , 56 59 ). Heat loss by evaporation can be enhanced by cooling techniques ( 35 , 40 , 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring T sk simultaneously with T c using the GI temperature pill during field exercise has not yet been investigated. The relationship between T sk and T c is not well understood due to physiological, endocrine, or vasomotor influences on both temperatures ( 25 , 56 , 59 ). Some studies have tried to correlate both T c and T sk ( 39 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Although only recently described in detail in racing thoroughbreds, [1][2][3][4] Brownlow has provided detailed clinical descriptions of the characteristics of this syndrome and termed it exertional heat illness (EHI) after a similar condition in human athletes. 2,[5][6][7] There is, however, minimal literature on the rates of occurrence and environmental risk factors for this syndrome. [1][2][3][4] Thoroughbred racing in temperate eastern Australia occurs over relatively short distances and durations.…”
mentioning
confidence: 99%